KMOS Clusters and VIRIAL GTO Surveys. Issue Volume 10:Issue S309(2014) (9th February 2015) - Wilman, D.; Bender, R.; Davies, R. L.; Mendel, J. T.; Chan, J.; Beifiori, A.; Houghton, R.; Saglia, R.; Schreiber, N. Förster; Wuyts, S.; van Dokkum, P.; Cappellari, M.; et al.
Abstract: We present the KMOS (K -bandM ulti-O bjectS pectrograph) Cluster and VIRIAL (V LTIR I FUA bsorptionL ine) Guaranteed Time Observation (GTO) programs. KMOS provides 24 arms each feeding an integral field unit (14×14 spaxels of 0.2″ pixels) for IZ, YJ, H and K band near infrared (NIR) medium resolution spectroscopy (R ∼ 3500). Targets are selected from a 7.2′ diameter patrol field. Ultra-deep spectroscopy of ∼ 80 early-type cluster galaxies (∼ 20hr on source) and ∼ 200 (∼ 10hr on source) early-type field galaxies at 1 < z < 2 will dramatically improve the situation at z > 1 for which measurements of stellar velocity dispersions and absorption indices are limited to a few, often relatively young passively evolving galaxies (e.g. Bezanson2013 ). In ESO Periods P92 and P93, 15 nights worth of data has been collected for KMOS-Clusters and 6 nights for VIRIAL: this will be supplemented with more data in upcoming semesters. All galaxies have multiband HST imaging including existing or upcoming WFC3 IR imaging, providing stellar mass maps and sizes. Combined with our dispersion measurements, this will allow us to examine the fundamental plane and the dynamical mass of a large sample of z > 1 galaxies for the first time, for both cluster and field galaxies.